ERGONOMIC RISK LEVEL OF MUSCULOSKELETAL DISORDERS (MSDS) COMPLAINTS IN SHILA SAWANGAN HOUSING PROJECT WORKERS IN DEPOK CITY IN 2023 - Rendy Andrianto; Triana Srisantyorini (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Musculoskeletal disorders is a disease that has complaints on skeletal muscles, these skeletal muscles are muscles that have a role as a skeletal mover. The study aimed to describe the level of ergonomic risk for the occurrence of musculoskeletal disorders (MSDS) in workers at the Shila Sawangan housing development project in Depok City in 2023. The type of research being conducted was quantitative descriptive research. The design used in this study is cross-sectional which is done by observing all work processes carried out and conducting interviews regarding MSDS complaints suffered by workers to assess the risk level of musculoskeletal disorders (MSDS) using the Rapid Entire Based Assessment (REBA) research tool and using the Nordic Body Map questionnaire (N.B.M.). Based on the results of the study, the age range of more than 30 years totaled 40 people with a percentage of 57%, the working period of 2 years and over totaled 47 people with a percentage of 67%, at a percentage of 79%, 55 workers did not exercise, as many as 73% of workers a total of 51 people did not stretch their muscles before starting work, then based on the results of the Nordic body Map questionnaire in the age range of 30 years and over there were only 38 workers experiencing complaints on body parts, while in the age range of 30 years and under there were 9 workers who experienced complaints on parts of the body, it is influenced by many factors such as working period, workload, physical activity, and body posture that is not ideal.